The victim’s remission in Brazilian legal penal culture in the XIX century: negotiation in the century of public justice? - Teixeira, Arley Fernandes (2019)
The present work has as its main objective the study of the victim’s remission, a criminal institute present in both Brazilian penal codes of the nineteenth century, Criminal Code of 1830 and Penal Code of 1890. The analysis is based, above all, on the legal books on criminal law and criminal procedural law of Brazil in the nineteenth century and seeks, firstly, to understand the legal functioning of this institute, the criteria of application and how works the part's capacity to forgive and, therefore, to close the process in progress and, from there, to enter into the most important doctrinal discussions on forgiveness, from which we highlight the problem of the miserable and the issue of slight physical offenses. All these discussions have the general purpose of understanding the role of criminal negotiations in Brazil during this period, which, although present throughout the nineteenth century, suffered a transformation in the end of this century. Finally, we sought to position these discussions and conclusions in the context of the formation of contemporary criminal law in Brazil, especially since the 1890s, a fundamental decade in this change.